1999
DOI: 10.1093/oxfordjournals.jbchem.a022283
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Measurements of Photovoltage Generation by Bacteriorhodopsin and Halorhodopsin Adsorbed on a Thin Polymer Film

Abstract: We constructed a time-resolved photovoltage measurement system and examined the photovoltage kinetics of wild-type bacteriorhodopsin, its D96N mutant, and halorhodopsins from Halobacterium salinarum and Natronobacterium pharaonis. Upon illumination with a laser flash, wild-type bacteriorhodopsin showed photovoltage generation with fast (10-100 micros range) and slow (ms range) components while D96N lacked the latter, as reported previously [Holz, M., Drachev, L.A., Mogi, T., Otto, H., Kaulen, A.D., Heyn, M.P.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
5
17
1
Order By: Relevance
“…Thus, the membrane potential appears to have significant effects on the Cl − transfer in the CP channel compared to those in the EC channel. This result might be consistent with previous reports: Ludmann et al [15] and Muneyuki et al [19] detected much smaller electrogenicity during the NpHR′ formation compared to that during the O formation. These observations may reflect the difference in dielectric constants of CP and EC channels.…”
Section: Electrogenic Processes During the Nphr Photocyclesupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, the membrane potential appears to have significant effects on the Cl − transfer in the CP channel compared to those in the EC channel. This result might be consistent with previous reports: Ludmann et al [15] and Muneyuki et al [19] detected much smaller electrogenicity during the NpHR′ formation compared to that during the O formation. These observations may reflect the difference in dielectric constants of CP and EC channels.…”
Section: Electrogenic Processes During the Nphr Photocyclesupporting
confidence: 94%
“…However, the previous flashinduced voltage measurements led to the conclusion that O does not appear in the Cl − transport photocycle [18]. On the other hand, other voltage measurements detected large electrogenicity during O formation [15,19]. These data support the model that Cl − release is associated with O formation.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Recently, time-resolved photovoltage analyses were reported for phR (15,26) and shR (26). In both phR and shR, major charge movement was observed in the millisecond time scale, and it was proposed that N (and/or O) intermediate formation was associated with charge movement (26).…”
Section: Discussionmentioning
confidence: 99%
“…HR is a light-driven, inward chloride pump associated with proton influx upon light activation (3,4), and the photocycle of HR includes the K, L, N, and O states (5,6). Among these series of intermediates, the process of chloride release occurs during the N-to-O-state transition (6)(7)(8)(9). It has been suggested that HR plays a significant biological role in either promoting the proton-motive force (10) to facilitate BR-assisted energy production, or maintaining a cellular osmolarity equilibrium (3,11) under the high-salinity environments found in their habitat.…”
Section: Introductionmentioning
confidence: 99%